Characterization of the inflammatory response to inhaled lipopolysaccharide in mild to moderate chronic obstructive pulmonary disease. (May 2015) - Gupta, Vandana; Banyard, Antonia; Mullan, Aoibheann; Sriskantharajah, Srividya; Southworth, Thomas; Singh, Dave
Abstract : Aims: Lipopolysaccharide (LPS) inhalation causes increased airway and systemic inflammation. We investigated LPS inhalation in patients with chronic obstructive pulmonary disease (COPD) as a model of bacterial exacerbations. We studied safety, changes in sputum and systemic biomarkers. We have also investigated interleukin (IL)‐17 concentrations in this model. Methods: Twelve COPD patients inhaled 5 μg LPS. Safety was monitored over 24 h. Sputum was induced at baseline, 6 and 24 h for cells and IL‐8, IL‐17, neutrophil elastase, monocyte chemoattractant protein‐1 (MCP‐1) and macrophage inflammatory protein‐1β (MIP‐1β) in supernatants. Serum was collected at baseline, 4, 8 and 24 h for IL‐6, C‐reactive protein (CRP) and Clara cell protein (CC‐16) concentrations. Peripheral blood mononuclear cells (PBMCs) were isolated at baseline and 4 h for systemic IL‐17 analysis. Results: LPS 5 μg was well tolerated. The greatest FEV1 change was 11.7% (mean) at 1 h (95% CI 5.1–18.2%). There was a large range in maximal fall (2.5–37.7%). Total sputum cell count and neutrophil count significantly increased 6 and 24 h post‐LPS. There was no change in sputum supernatant mediators. IL‐6, CRP and CC‐16 increased post‐inhalation, with different temporal patterns. CD4+ and CD8+ cell associated IL‐17 significantly increased at 4 h. Conclusions: Inhaled LPS in COPD patients safely causes increased airway and systemic inflammation. This may be a model for studying COPD exacerbations.